Optimization of governance model of post-food harest and distribution in msme centers in 5 subdistricts in sidoarjo regency - JFX Susanto Soekiman; Agus Baktiono; I Putu Artaya (Universitas Hayam Wuruk Perbanas, 2017)
The purpose of this research is to formulate the model of post-harvest food commodity governance and its distribution management in 5 districts of Sidoarjo Regency, so that the center of MSMEs can give real contribution to the food commodity resilience program and able to maintain the stability of food commodity availability evenly throughout Sidoarjo regency. The research method used in this research is quantitative descriptive in the form of fact finding with proper interpretation. The results show that food availability is increasingly limited due to increased conversion of paddy fields and other productive agricultural land, low productivity of agricultural products, poor irrigation networks and irrigation infrastructure in production areas has become a serious threat to the sustainability of food self-sufficiency. Similarly, the phenomenon of harvested area and paddy production in 5 sub-districts (Krembung, Tulangan, Balungbendo, Prambon, and Tarik) for the period of 2000s have fluctuated so that in the long term it will greatly disrupt the food security in the region Sidoarjo Regency. Therefore, there is a need for seriously arranging the governance of food commodities (rice) post-harvest and distribution governance.